1995
DOI: 10.1088/0953-8984/7/10/028
|View full text |Cite
|
Sign up to set email alerts
|

ENDOR investigation of cubic Fe3+centres in NaCl single crystals

Abstract: Cubic Fe3+ centres in NaCl single crystals have been studied with electron nuclear double resonance (ENDOR) at T=17 K. The superhyperfine (SHF) and quadrupole interactions of the paramagnetic ion with the nearest set of four Cl- anions and the second-nearest set of twelve Na+. Cations have been determined. The results confirm the structural model of an Fe3+ ion at a tetrahedrally symmetric interstitial position with the nearest four Na+ cations missing, as suggested previously from the analysis of the SHF stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…By further annealing above 250 K or by x-irradiation at room temperature (RT), the orthorhombic Fe 3+ centres are converted into cubic Fe 3+ cub centres. As suggested previously from the analysis of the EPR superhyperfine (shf ) structure [6], and recently confirmed by electron-nuclear double-resonance (ENDOR) spectroscopy [7], the Fe 3+ cub centre consists of an interstitial Fe 3+ ion with its four nearest Na + neighbours missing. As far as we are aware, the presence of such an interstitial cation in the compact NaCl lattice which is known to exhibit a predominant Schottky type of disorder [8] had not been reported before.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…By further annealing above 250 K or by x-irradiation at room temperature (RT), the orthorhombic Fe 3+ centres are converted into cubic Fe 3+ cub centres. As suggested previously from the analysis of the EPR superhyperfine (shf ) structure [6], and recently confirmed by electron-nuclear double-resonance (ENDOR) spectroscopy [7], the Fe 3+ cub centre consists of an interstitial Fe 3+ ion with its four nearest Na + neighbours missing. As far as we are aware, the presence of such an interstitial cation in the compact NaCl lattice which is known to exhibit a predominant Schottky type of disorder [8] had not been reported before.…”
Section: Introductionmentioning
confidence: 81%
“…Compared to the case for the cubic Fe 3+ centres studied previously [7], ENDOR measurements of the orthorhombic Fe 3+ (I) centres are complicated by the fact that, due to the large ZFS parameters, the EPR transitions extend over a large magnetic field range and are highly anisotropic. The EPR lines labelled x, y, and z in figure 1 were chosen for the ENDOR measurements because in the X band they are well separated from the other lines as well as from the EPR lines of the Fe + centre.…”
Section: Endor Measurementsmentioning
confidence: 90%
See 1 more Smart Citation
“…Also, Hay et al [6] showed that lowtemperature irradiation with band-gap light could also produce a trigonally symmetric centre, Fe 3+ trig , with only three cation vacancies bound to the interstitial Fe 3+ ; at higher temperatures, this converts to the cubic centre Fe 3+ cubic , described above. The cubic centre is apparently stabilized by the binding energy of the tetrachloroferrate ion; it has also since been seen in other hosts, such as Fe-doped NaCl [7][8][9].…”
Section: Formation Of the Interstitial Ferric Defectsmentioning
confidence: 99%
“…Sodium chlorine (NaCl) single crystal is usually regarded as a model system for investigations of the structural and magnetic properties of the doped transition-metal impurities. Especially, NaCl containing iron exhibit interesting magnetoplastic [1], crystallization [2] and electronic and local relaxation [3] properties as well as unique magnetic resonance and electron nuclear double resonance behaviours [4][5][6]. These properties or behaviours may be closely related to the local crystal field environments of the doped iron impurities in the hosts, and the above properties can be conveniently studied by means of the electron paramagnetic resonance (EPR) technique.…”
Section: Introductionmentioning
confidence: 99%